2017
DOI: 10.3390/ijgi6110365
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Model for Co-Seismic Landslide Susceptibility Using GIS and Random Forest Method

Abstract: Abstract:The Mw 7.8 Gorkha earthquake of 25 April 2015 triggered thousands of landslides in the central part of the Nepal Himalayas. The main goal of this study was to generate an ensemble-based map of co-seismic landslide susceptibility in Sindhupalchowk District using model comparison and combination strands. A total of 2194 co-seismic landslides were identified and were randomly split into 1536 (~70%), to train data for establishing the model, and the remaining 658 (~30%) for the validation of the model. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Therefore, in the present study, three classification algorithms (RF, XGBoost and DNN) were utilized and compared for landslide susceptibility mapping at Inje area. Basically, the RF model is one of the popular and widely used models to make landslide susceptibility [60,81,82] and on other hand, XGBoost and DNN had been explored in limited studies for spatial prediction of occurrence of the landslide, which showed promising results in the study area. Regard to important IFs, three models revealed that horizontal drainage proximity (h) is the most important IF among 13 IFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, three classification algorithms (RF, XGBoost and DNN) were utilized and compared for landslide susceptibility mapping at Inje area. Basically, the RF model is one of the popular and widely used models to make landslide susceptibility [60,81,82] and on other hand, XGBoost and DNN had been explored in limited studies for spatial prediction of occurrence of the landslide, which showed promising results in the study area. Regard to important IFs, three models revealed that horizontal drainage proximity (h) is the most important IF among 13 IFs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies illustrated that RF method can adequately depict probable occurrence of landslide and spatial data [81,82,86,87]. There are several pieces of research on landslide susceptibility using a gradient boosting algorithm [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability assessments have been conducted for natural disasters other than earthquakes, including floods [22][23][24][25][26], landslides [27][28][29][30][31][32][33][34], gully erosion [35][36][37][38][39], and groundwater contamination [40][41][42][43][44]. Some studies have compared the performance of various methodologies, including probabilistic techniques such as frequency ratio (FR) models [22,27,43], statistical techniques such as LR-based models [22,27,28,32,34,38,[40][41][42][43], and machine learning algorithms such as decision tree (DT) [24,26,28,29,31,34,38,39,[42][43][44], random forest (RF) …”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, many studies of natural disasters have implemented various methods to evaluate vulnerability and susceptibility, resulting in the development of risk-assessment maps. These methods have included probabilistic and statistical methodologies [15][16][17][18][19] and machine learning approaches [20][21][22][23][24][25][26][27]. Recent research has actively compared the suitability of machine-learning methodologies [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%